Institutionalization of Algorithmic Tabayyun: Integration of Maqashid Sharia as the Philosophical Foundation for Regulation of Transnational Media Platforms - Suhaily Amri Hasibuan; Hasan Sazali; Muhammad Randicha Hamandia; Zhila Jannati (Indonesian Journal Publisher, 2026)
The rapid growth of synthetic media, deepfakes, generative artificial intelligence, and transnational platform algorithms has produced a crisis of digital authenticity, where public communication is increasingly shaped by opaque systems that blur truth, manipulation, and fabrication. This study formulates Algorithmic Tabayyun as a normative framework for Islamic communication ethics and transnational media governance. Using qualitative library research, critical discourse analysis, and thematic Qur’anic interpretation, it examines synthetic media, algorithmic accountability, platform regulation, and Maqasid Sharia. The findings show that secular regulatory models remain limited because they frame digital harm as technical, administrative, or post-facto legal problems, while overlooking moral responsibility, human dignity, public reason, and corporate intention behind engagement-driven algorithms. Algorithmic Tabayyun expands Qur’anic information verification from individual ethics into institutional mechanisms requiring source validation, algorithmic transparency, bias detection, and social impact assessment. By integrating Maqasid Sharia, it protects reason, religion, dignity, privacy, and wealth from misinformation, hate speech, reputational harm, and surveillance capitalism across national, regional, and global regulatory contexts today. These reforms strengthen accountability within contemporary digital societies